Semantic Extensions and Loan Shift Extensions in Bahasa Malaysia Resulting from Contact with English - Lee Hsia Carmel Heah (Journal of Modern Languages)
This study attempts to find the effect of the contact with English on semantic extensions and loan shift extensions in Bahasa Malaysia. It considers this believe of some scholars who mention that it is axiomatic that when a foreign cultural item (material or non-material) is borrowed, the designation for it is simultaneously borrowed as well. The paper states that the semantically extended terms suggest a correlation between linguistic change and socio cultural economic political change.